2007
DOI: 10.1111/j.1365-2400.2007.00560.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of catches and harvest of recreational shore angling in the north of Portugal

Abstract: Recreational shore angling in the Atlantic Ocean between Moledo and Aveiro (Portugal) was examined using roving creel surveys (March/September 2001). Cooperation was high (90% of 2310 anglers approached). At least 39 species of fish were caught at a rate of approximately 0.5 fish angler h )1 . An estimated 7319 kg of Dicentrarchus labrax (L.), with 45.6% below the minimum legal size, and 2040 kg of sea breams (genus Diplodus), correspond to 5.75% and 1.19% of the commercial landings in the same geographical ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 36 publications
(49 reference statements)
8
47
3
Order By: Relevance
“…While this contradicts the opinions and beliefs of anglers interviewed both in the north and south of Portugal (Rangel andErzini 2007, Veiga et al 2010), an explanation can be found in the differences between recreational and sport angling. In the latter, the anglers in competitions focus on the more abundant pelagic fish (chub mackerel and garfish) and mullets, which have little or no commercial value, in order to maximise their catches, whereas recreational anglers target the more highly prized sea breams and European seabass that are also heavily fished by the commercial fishermen.…”
Section: Resultsmentioning
confidence: 46%
See 4 more Smart Citations
“…While this contradicts the opinions and beliefs of anglers interviewed both in the north and south of Portugal (Rangel andErzini 2007, Veiga et al 2010), an explanation can be found in the differences between recreational and sport angling. In the latter, the anglers in competitions focus on the more abundant pelagic fish (chub mackerel and garfish) and mullets, which have little or no commercial value, in order to maximise their catches, whereas recreational anglers target the more highly prized sea breams and European seabass that are also heavily fished by the commercial fishermen.…”
Section: Resultsmentioning
confidence: 46%
“…(Table 1). In comparison, Rangel and Erzini (2007), in the northern Portugal beach angling, identified sea bream Diplodus spp. and European seabass, Dicentrarchus labrax (L.), as the most important species caught by recreational anglers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations